2019
DOI: 10.1021/acsomega.9b00619
|View full text |Cite
|
Sign up to set email alerts
|

Optical Stability of 1,1′-Binaphthyl Derivatives

Abstract: The racemization process of various 1,1′-binaphthyl derivatives is studied by quantum calculations. The preferred racemization pathway passes through a transition state belonging to the C i symmetry group. The energy barrier for this process is independent of solvation, the electron-withdrawing/releasing power of substituents, or their ability to engage in H-bonds within the molecule. The primary factor is instead the substituent size. The barrier is thus reduced when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…A recent study by Tkachenko et al used three DFT methods (PBE0, B3LYP and TPSSh) with the Pople augmented basis set 6‐311+G* plus the implemented MP4/cc‐pVDZ//B3LYP/6‐311+G* level of theory. The study confirmed that the racemization of BINOL passes through a preferred anti‐Ci transition state with an energy of 164 kJ/mol and a strong deformation of the aromatic system …”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…A recent study by Tkachenko et al used three DFT methods (PBE0, B3LYP and TPSSh) with the Pople augmented basis set 6‐311+G* plus the implemented MP4/cc‐pVDZ//B3LYP/6‐311+G* level of theory. The study confirmed that the racemization of BINOL passes through a preferred anti‐Ci transition state with an energy of 164 kJ/mol and a strong deformation of the aromatic system …”
Section: Resultssupporting
confidence: 53%
“…The study confirmed that the racemization of BINOL passes through a preferred anti-Ci transition state with an energy of 164 kJ/mol and a strong deformation of the aromatic system. [20] While BINOL has considerable stability under neutral conditions, it is often stated to readily racemize in both acidic and basic solutions. [2,21] In acids, the protonation of the C1 atom gives a cationic species in which the naphthyl rings can rotate about a C(sp2)-C(sp3) bond.…”
Section: Racemization Of Binolmentioning
confidence: 99%
“…We begin by examining the uncatalyzed and graphenecatalyzed chirality inversions of BINOL in solution. A number of DFT studies have considered the inversion of binaphthyl derivatives (including BINOL) in the gas-phase [8,[34][35][36] and established that racemization consistently proceeds through a kinetically preferred anti-type transition structure with C i symmetry. Therefore, we focus here on the anti-type reaction pathway.…”
Section: Solvent Effects On the Graphene-catalyzed Racemization Of Binolmentioning
confidence: 99%
“…Being one of the most common motifs in the backbones of asymmetric metal and organocatalysts, the racemizations of biaryl compounds have been studied extensively both computationally and experimentally. Here, we focus on the racemizations of 1,1′-binaphthyl ( 1 ) and its synthetically highly relevant derivative 1,1′-binaphthyl-2,2′-diol (BINOL) ( 2 ) which forms the starting material to a myriad of chiral catalysts. Table gives experimentally determined rotational barriers for compounds 1 and 2 .…”
mentioning
confidence: 99%